Studi Perbandingan Sistem Bagi Hasil Perikanan Lokal dengan Undang Undang Bagi Hasil Perikanan di Kecamatan Labuan; Jawa Barat - Achmad Fahrudin; Dinarwan *.; Istiqlaliyah Muflikhati; Gatot Yulianto (Buletin Ekonomi Perikanan, 1996)
Indonesian government released Fisheries Sharing Law (UU Bagi Hasil Perikanan No. 16/1964) to avoid income gap among fishermen. But local fisheries sharing system stilI applied in some areas. These facts supported the research to find the reasons of institutionalization failure of fisheries sharing law. Research gain indicated that local fisheries sharing system used the same way to calculated net product among fishing gears, but different way in shared net product between owner and tenant in each gear. Fisheries sharing law used the same way to calculated net product and the same way in shared net product between owner and tenant in every fishing gear. This law were not favourable especially by the owners of gillnet and trammel net because their income will be decreased if they used it. Both fisheries sharing systems still made income gap between owner and tenant in each fishing gear and economically not suitable because unequality between opportunity and gain. Based on this comparative study, it is important to applied alternative sharing system which gave equality in product shared and economically consequences.